Observations of hypomelanosis in the nurse shark Ginglymostoma cirratum. Issue 1 (2nd November 2022) - Shipley, Oliver N.; Fitzgerald, Jamie; Horne, Bryan; Crowe, Steven; Gallagher, Austin J.
Abstract: Hypomelanosis refers to a suite of skin pigment abnormalities, including albinism, leucism and piebaldism. While documented across many vertebrate species, examples of hypomelanosis are rarely seen in chondrichthyans, with little insight into the potential effects on survival. Here, we report the first observation of abnormal skin pigmentation indicative of piebaldism in the Atlantic nurse shark Ginglymostoma cirratum, representing only the second reported case of skin aberrations for this species. This extremely rare observation is discussed in the broader context of fitness variation and long‐term survival.